PENGARUH LATIHAN CROSSING HEADING TERHADAP KEMAMPUAN HEADING TIM SEPAKBOLA SMA OLAHRAGA MASMUR PEKANBARU - Randy Arbertha; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: The problem in this research is that during soccer match players are not good at headings, this in seen when dueling the ball in the air and directing the ball toward the opponent’s goal. This type of research is a kind of experimental research to see the effect of the form of exercise. The purpose of this research is to look at the effect of crossing heading training on the ability of heading high school sports football team masmur Pekanbaru. The population in this research was the players football team high school sports Masmur Pekanbaru, with a total of total 22 people. The sampling technique is to use total sampling. Data collection techniques were obtained from the pre-test and post-test. The instrument in this research used the ball playing test with the head as a tool to measure the ability of heading. The data is then statistically processed to test the normality using the lilifours test at a significant level of 0.05a based on the analysis of the normality of the data X, it gives LoMax of 0.151 and Ltable 0.190, this means LoMax<Ltable. While the variable Y yields LoMax of 0.167 and Ltable 0.190, this means LoMax<Ltable. The analysis was performed by t-test. On the basis of data analysis and discussion it can be concluded that there is an effect of crossing heading training on the ability of heading football team High School Sports Masmur Pekanbaru proven by Tcount of 16,72 and Ttable 1,721. Means Tcount > Ttabel at the level a = 0.05.Key Words: Crossing Heading, Ability Heading